Morphotectonic analysis of faults in Sperchios Basin (Fthiotis, Central Greece). - Michail, M.; Chatzipetros, A. (Bulletin of the Geological Society of Greece, 2013)
This paper aims to study one of the major neotectonic, fault-controlled, features of the Hellenides, Sperchios basin, with the application of specific morphotectonic indices. The study area includes well exposed fault-bounded mountain fronts with dominant footwall relief. The most prominent structures of this WNW-ESE trending neotectonic basin are WNW-ESE to NW-SE trending faults, the most prominent of which is the Sperchios Fault System (SFS) causing mainly subsidence toward the NNE. The antithetic Coastal Fault System (CFS) also forms a distinct, yet gentler relief at the NE basin boundary. The segmentation of these neotectonic faults allowed detailed measurements, based on morphotectonic characteristics, of each segment separately. Mountain-front sinuosity (Smf) as well as the ratio of valley floor width to valley height (Vf) were among the indices used in this study and contributed to the identification of the potential fault activity. The results show that there is a strong correlation between uplift rates and the morphotectonic signature of faulting, as well as a clear morphotectonic differentiation of fault segments.